2021
DOI: 10.9734/jpri/2021/v33i35a31886
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sports Injuries before and during COVID-19 Quarantine among Adults of Riyadh, Saudi Arabia

Abstract: Aims: This study aims to compare the incident rate of sports injuries before and during the COVID-19 quarantine among active and nonactive adults and identify and compare patterns, types and sites of sports injuries. Study Design: Cross-sectional study. Place and Duration of Study: A self-administered online survey was conducted in Riyadh, Saudi Arabia, between June 2020 to November 2020. Methodology: We conducted a descriptive, cross-sectional web-based survey on active and nonactive adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…1,7 However, some studies conducted during this period have also shown that injuries can be reduced when returning to the season after isolation and quarantine. 17,18 Bisciotti et al 1 stated that after the COVID-19 pandemic, in returning to the season in football, important problems such as loss of performance, increased risk of injury, and the consequences of systemic changes may be encountered due to the lack of training brought about by social isolation measures. Mannino et al 19 on the other hand stated that injuries increased in the 2020-2021 season affected by the pandemic, and the reason for this could be a tight fixture.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 However, some studies conducted during this period have also shown that injuries can be reduced when returning to the season after isolation and quarantine. 17,18 Bisciotti et al 1 stated that after the COVID-19 pandemic, in returning to the season in football, important problems such as loss of performance, increased risk of injury, and the consequences of systemic changes may be encountered due to the lack of training brought about by social isolation measures. Mannino et al 19 on the other hand stated that injuries increased in the 2020-2021 season affected by the pandemic, and the reason for this could be a tight fixture.…”
Section: Discussionmentioning
confidence: 99%